PERBANDINGAN EFEKTIFITAS ASAM FOLAT DOSIS STANDAR DENGAN DOSIS TINGGI TERHADAP HIPERHOMOSISTEINEMIA PADA GAGAL GINJAL DENGAN HEMODIALISIS REGULER - Darmaja, I Made Gede; Suwitra, Ketut (journal of internal medicine, 2006)
Prevalence of hyperhomocysteinemia(HHcy) in regularly hemodialysis chronic kidney disease (RHDCKD) is high.HHcy in RHD CKD related to atherosclerosis an increase risk of cardiovascular disease. Increasing 5 ?mol/L of Hcy level from10?mol/L correlate with increasing 60% cardiovascular risk in male and 80% in female and also increasing 50% risk of strokeboth in male and female. Folic acid, vitamin B 12 and vitamin B 6 is needed to decrease Hcy level according homocysteine trialystlowering collaboration (HTLC), folic acid may decrease the Hcy level by 25%, vitamin B 12 7% but no significance effect ofvitamin B 6. Standard dose of folic acid 2-5 mg/day may normalized HHcy in predialysis CKD but most of RHDCKD fail toreach normal level. Treatment result of RHDCKD before is varied and inconsistent. This study was randomized double blindcontrolled clinical trial aimed to know whether higher dose of folic acid decreased Hcy greater than standard dose, that using 15mg/day compare to 5 mg/day of folic acid treatment for 4 weeks RHDCKD with hyperhomocysteinemia. Thirty patients wererecruited base on exclusion and inclusion criteria and two weeks standardization using 1 mg/day folic acid was performed.Complete blood count, lipid profile, blood sugar, albumin and globulin, BUN, creatinine serum, SGPT/SGOT and Hcy wereexamined in the beginning of the study and after 4 weeks. Permuted block randomization was done among participant in order togrouping them into 15 mg/day and 5 mg/day folic acid group. Compare means of decreased Hcy in each group as primaryoutcome was analyzed using student t test, 95% confidence interval (CI) , p<0,05. During study, 15 patients were treated with 15mg/day folic acid and 13 patients with 5 mg/day folic acid. Increased of Hcy was 1,00±4,11 ?Mol/L among 15 mg/day folic acidgroup (20,67 ±6,69 ?Mol/L increased to 21,68±4,59 ?Mol/L ) and 1,93±3,40 ?Mol/L (18,77±5,38 increased to21,00±5,24?Mol/L) among 5 mg /day folic acid group, CI 95% -2,03 to 3,88, p = 0,53. ANCOVA analyzed of other variableseffect such as BMI, blood sugar, age and sex on Hcy level was not found. We conclude that 15 mg/day comparing to 5 mg/dayfolic acid is not more effective in decreasing Hcy level of regularly hemodialysed patient with hyperhomocysteinemia.